Tumoral Prostate Shows Different Expression Pattern of Somatostatin Receptor 2 (SSTR2) and Phosphotyrosine Phosphatase SHP-1 (PTPN6) According to Tumor Progression. (8th April 2009) - Cariaga-Martinez, Ariel Ernesto; Lorenzati, María Angelica; Riera, Mario Alejandro; Cubilla, Marisa Angelica; De La Rossa, Andrés; Giorgio, Ernesto Martín; Tiscornia, María Mercedes; Gimenez, Esteban Mariano; Rojas, María Eugenia; Chaneton, Bárbara Julieta; Rodríguez, Dora Isabel; Zapata, Pedro Darío
Abstract : Prostate proliferation is dependent of androgens and many peptide hormones. Recent reports suggest that SSTR2 and SHP-1 were two fundamental components on antiproliferative effect of somatostatin. Many studies on SHP-1 revealed that the expression of this protein was diminished or abolished in several of the cancer cell lines and tissues examined. However, it is necessary to confront the cell lines data with real situation in cancer cases. Our studies have shown that epithelial expressions of both proteins, SHP-1 and SSTR2, in normal and benign hyperplasia are localized in the luminal side of duct and acinar cells. Also, SSTR2 is expressed in stromal cells. In malignant prostate tissue, SHP-1 was diminished in 28/45 cases or absent in 12/45 cases, whereas SSTR2 epithelial was diminished in 38/45 cases or lost in only 2/45 cases. The intensity of immunostained was highly negative correlated with Gleason grade for two proteins.